DETERMINING THE MEDIATING ROLE OF DIVIDEND POLICY IN THE IMPACT OF FINANCIAL PERFORMANCE AND CAPITAL STRUCTURE ON THE VALUE OF COMPANIES ACCEPTED ON THE IRAQ STOCK EXCHANGE - Muhammad Adnan Hamoud Fayyad Al-Hamdani (Scholar Express Journals, 2024)
The research aims to shed light on the mediating role of dividend policy and the extent of its impact on financial performance and capital structure on the value of companies accepted on the Iraq Stock Exchange. In order to achieve the goal of the research, it relies on the use of the descriptive analytical approach, which helps in clarifying the relationship between the research variables. This is the use of statistical analysis tools that suit the nature of the research data, and the study reached many results, There is a statistically significant effect of :the most important of which are the mediating role of the dividend policy on the impact of financial performance and capital structure on the value of companies accepted in the Iraq Stock Exchange at 0.05, which demonstrates the validity of the main hypothesis of the study and shows that there is a statistically significant effect at 0.05 for both the dividend policy and financial performance on the market value of the company. While it was found that there was no statistically significant effect of the capital structure on the company’s market value at 0.05, it became clear that whenever the level of the dividend distribution policy increased by 1%, the company’s market value increased by 0.473%, and that whenever the level of financial performance increased by 1%, the company’s market value increased by 0.437%. The research also recommends the necessity of working to increase the level of awareness of company management about the necessity of paying attention to the dividend distribution policy and working to develop it.
Keywords: dividend distribution; financial performance; capital structure